METODELOGI MAQASHID AL-SYARI’AH JASSER AUDA SEBAGAI PENDEKATAN BARU SISTEM HUKUM ISLAM - Dedisyah Putra; Asrul Hamid; Martua Nasution (AL-SYAKHSHIYYAH Jurnal Hukum Keluarga Islam dan Kemanusiaan, 2022)
AbstractMaqasid al-Sharia is one of the discourses in the study of fiqh thought, both traditional and contemporary. However, in its development experienced various challenges and problems that surround it. Some of the problems that arise are that ushul fiqh is considered too textual and ignores the purpose of the text. Thus, it makes the purpose of making sharia laws or decisions not in accordance with the context. In this case, Jasser Auda tries to make an effort to criticize this issue. On the other hand, there are some weaknesses in the maqasid theory which does not provide details on certain chapters or problems. So that these conditions are considered unable to provide detailed answers to certain problems. Therefore, in this study, attempts to re-construct and make improvements with various approaches and methodologies initiated by Jasser Auda. Qualitative research methods are used in this study to examine various literatures related to the data that support this research, especially related to the renewal methodology carried out by Jasser Auda in analyzing maqasid al-shariah. This study found that in fact the perspective of the old maqasid concept to the new maqasid, that is, if you look at the classical paradigm, it lies in efforts to protect and guard or preserve. Meanwhile, if you look at the contemporary paradigm, it focuses more on the development and right side.Keywords: Islamic Law; Jasser Auda; Methodology; Maqasid al-Shariah.